Coating with cationic inulin enhances the drug release profile and in vitro anticancer activity of lecithin-based nano drug delivery systems - EROĞLU, MEHMET SAYIP (My University, 2023)
Core-shell structured lipidic nanoparticles (LNPs) were developed using lecithin sodium acetate (Lec-OAc) ionic complex as a core unit and quaternized inulin (QIn) as the shell part. Inulin (In) was modified using glycidyl trimethyl ammonium chloride (GTMAC) as a positively charged shell part and used for coating the negatively surface charged Lec-OAc. The critical micelle concentration (CMC) of the core was determined as 1.047 × 10−4 M, which is expected to provide high stability in blood circulation as a drug-carrying compartment. The amounts of curcumin (Cur) and paclitaxel (Ptx) loaded to LNPs (CurPtx-LNPs), and quaternized inulin-coated LNPs (Cur-Ptx-QIn-LNPs) were optimized to obtain mono-dispersed particles with maximum payload. The total amount of 2.0 mg of the drug mixture (1 mg Cur and 1 mg Ptx) was the optimized quantity for QIn-LNPs and CurPtx-QIn-LNPs due to the favorable physicochemical properties determined by dynamic light scattering (DLS) studies. This inference was confirmed by differential scanning calorimeter (DSC), and Fourier-transform infrared (FT-IR). SEM and TEM images clearly revealed the spherical shapes of LNPs and QIn-LNPs, and QIn covered the LNPs completely. The cumulative release measurements of Cur and Ptx from CurPtx-QIn-LNPs, along with the kinetic studies, showed a significant decrease in the release period of drug molecules with the effect of the coating. At the same time, Korsmeyer-Peppas was the best diffusion-controlled release model. Coating of the LNPs with QIn increased the cell-internalization of NPs to the MDA-MB-231 breast cancer cell lines, resulting in a better toxicity profile than the empty LNPs.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Yaşam Bilimleri (LIFE); BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; BIOCHEMISTRY & MOLECULAR BIOLOGY; Yapısal Biyoloji; Biyokimya; Moleküler Biyoloji; Structural Biology; Biochemistry; Molecular Biology; Drug delivery systems; Inulin, drug release kinetics; Lecithin; Solid lipid nanoparticles